Assessing habitat selection of grassland rodents in the Cradle of Humankind - Pinto, Catiuscia-Jade (University of the Witwatersrand, Johannesburg, 2024)
Habitat selection is a decision-making process undertaken by animals to select an appropriate environment suitable for fulfilling their survival and reproductive needs. These decisions are driven by a complex of biotic and abiotic factors. Habitat selection relies on how an animal interacts with its environment and is species-specific. The vegetation structure and composition influence how smaller animals, such as rodents, obtain food and cover, and are thus critical for their survival. The aim of my study was to assess the population demography and habitat selection of nocturnal rodents in two grassland sites located within the Cradle of Humankind Nature Reserve, Krugersdorp, Gauteng Province, South Africa. I obtained rodent data using Capture-Mark-Recapture (CMR) methods, and vegetation data were obtained through randomised quadrate sampling. The following six rodent species were sampled, Gerbilliscus leucogaster, Lemniscomys rosalia, Mastomys coucha, Micaelamys namaquensis, Mus minutoides and Otomys angoniensis. Rodent abundance differed between summer and winter, with winter showing a higher abundance, but richness and diversity indices did not differ significantly between sites or seasons. The three most common species, G. leucogaster, M. coucha and O. angoniensis, were selected for further population demography analyses. The demography of G. leucogaster, was mostly associated with the season since seasonal fluctuations were observed in their population size (higher in summer), reproductive activity (more active in summer) and body condition (higher in winter). Mastomys coucha was the most abundant species in the study, since it had the highest number of sampled individuals in both summer and winter, although its demography was not influenced by external factors (e.g.,, season, vegetation height, vegetation cover) recorded in both summer and winter. Otomys angoniensis had a positive relationship with vegetation height and rodents’ body condition. The three species were able to coexist with one another due to differences in foraging strategies, reproductive strategies, spatial and dietary partitioning, which help to facilitate habitat selection and illustrate that habitat selection is species specific. Key words: Rodents, habitat selection, Gerbilliscus leucogaster, Mastomys couch
A research report submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Rodents; Gerbilliscus leucogaster; Mastomys coucha; Life on land; SDG-4: Quality education